(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This study aimed at finding out the differences in item difficulty parameter estimations for Simulated Data having (MC1- PL) Model in Item Response Theory (IRT) according to the differences in a test Dimensions (3D; 2D; 1D), correlations between these dimensions (0.0, 0.50, 0.86), and the statistical program used in analyzing the data (NOHARM؛ Bilog- MG3). The Monte Carlo simulations data having (MC1- PL) Model in IRT using (RESGENT) program; that fully filled in a 21-item was used to achieve the study aims. Data were analyzed using the statistical programs (NOHARM؛ Bilog- MG3). The results revealed no statistically significant differences in item difficulty parameter estimations that construct the multidimensional test within items due to differences in a test, correlations between these dimensions, and the statistical program used in analyzing the data (NOHARM؛ Bilog- MG3), as well as the estimations were consistent and high. Finally, the study recommends using these statistical programs for a data having (MC1- PL) Model, especially when similar assumptions are satisfied in a real data.